Sex differences in the rates of incident and recurrent coronary heart disease and all-cause mortality. (25th November 2020) - Peters, S; Colantonio, L; Chen, L; Bittner, V; Farkouh, M; Dluzniewski, P; Poudel, B; Muntner, P; Woodward, M
Abstract: Background: Women have lower age-specific rates of incident coronary heart disease (CHD) than men. However, it remains unclear whether women maintain the same advantage once they have had a cardiac event. Purpose: To assess whether sex differences in the rates of cardiac events and all-cause mortality among individuals without a history of CHD persist following a myocardial infarction (MI). Methods: We identified 171, 897 women and 167, 993 men <65 years of age with commercial health insurance and ≥66 years of age with government health insurance through Medicare who had a MI hospitalization between 2015 and 2016 in the US. These beneficiaries were matched to 687, 588 women and 671, 972 men without a history of CHD based on age and calendar year. Beneficiaries were followed until December 2017 for the occurrence of MI, CHD, heart failure, and all-cause mortality (Medicare only). Results: The age-standardized rates of MI per 1, 000 person-years were 4.5 in women and 5.7 in men without a history of CHD (multivariable-adjusted hazard ratio [HR] [95% confidence interval] of female sex: 0.64 [0.62; 0.67]) and 60.2 in women and 59.8 in men with a history of MI (HR: 0.94 [0.92, 0.96]) (Figure 1). Rates of CHD events in women vs. men were 6.3 vs. 10.7 among those without CHD (HR: 0.53 [0.51, 0.54]) and 84.5 vs. 99.3 among those with MI (HR: 0.87 [0.85, 0.89]). Heart failure hospitalization rates in women vs. men were 9.3 vs. 6.6 for those without CHD (HR: 0.93 [0.90, 0.96]) and 114.9 vs. 97.9 among those with MI (HR: 1.02 [1.00, 1.04]). All-cause mortality rates in women vs. men were 63.7 vs. 59.0 among those without CHD (HR: 0.72 [0.71; 0.73]) and 311.6 vs. 284.5 among those with a MI (HR: 0.90 [0.89, 0.92]). Conclusion: The women advantage against MI, CHD, heart failure and all-cause mortality is considerably attenuated following a MI, suggesting that a prior MI puts women at almost the same high-risk of subsequent events as men. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): This work was funded by an industry/academic collaboration between Amgen Inc. and University of Alabama at Birmingham.